KUALITAS LAYANAN SEBAGAI VARIABEL MEDIASI PENGARUH KUALITAS PRODUKSI TERHADAP KEPUASAN PELANGGAN E-COMMERCE - Neneng Masnun (Prodi Ekonomi Pembangunan, Universitas Muhammadiyah Berau, 2026)
This research aims to examine how production quality influences customer satisfaction, with service quality acting as a mediating variable within the e-commerce sector in Bulungan Regency, North Kalimantan. The rise in digital transactions in this area has been accompanied by frequent customer complaints related to both product quality and service, highlighting the need for an empirical investigation into the factors shaping customer satisfaction. The study adopts a quantitative approach using the Partial Least Squares–Structural Equation Modeling (PLS-SEM) technique with the WarpPLS 8.0 software. The sample consists of 75 active e-commerce users in Bulungan Regency, selected through purposive sampling. The findings reveal that production quality positively and significantly affects customer satisfaction and also has a positive effect on service quality. In addition, service quality positively and significantly impacts customer satisfaction and serves as a mediator in the relationship between production quality and customer satisfaction. These results underscore that enhancing product quality must be accompanied by improvements in service quality to achieve long-term customer satisfaction in e-commerce markets within developing regions.